Percutaneous edge-to-edge repair of mitral regurgitation as a bail-out strategy in critically Ill patients - Pleger, Sven Torsten; Chorianopoulos, Emmanuel; Krumsdorf, Ulrike; Katus, Hugo; Bekeredjian, Raffi (The journal of invasive cardiology, 2013)
Percutaneous edge-to-edge mitral valve repair using the MitraClip device has evolved as a new tool for the treatment of severe mitral valve regurgitation. This technique has been evaluated in both surgical low- and high-risk patients. The aim of this study was to assess the feasibility and efficacy of MitraClip implantation in critically ill, unstable patients with severe mitral regurgitation who would persistently need inotropes or who could not be weaned from a ventilator. Six patients with the above-mentioned criteria were identified among the 87 patients that were treated with MitraClip implantation between October 2009 and January 2012 at our institution. All patients were considered as surgical high-risk patients with a Society of Thoracic Surgeons (STS) score between 8.0% and 56.9%. In all patients, MitraClip implantation was successfully achieved without relevant complications. More importantly, all patients showed rapid clinical improvement within a few days, allowing discontinuation of inotropes and/or weaning from a respirator and finally a transfer to a regular ward or discharge home. These data emphasize the safety profile of the MitraClip system in multimorbid, high-risk patients. In addition, it demonstrates the applicability of this treatment in unstable and critically ill conditions as a tool for acute stabilization.
Keine DOI vorhanden
Gesehen am 10.01.2022